2006
DOI: 10.1080/00397910600770821
|View full text |Cite
|
Sign up to set email alerts
|

Mild Oxidation of Alcohols with o‐Iodoxybenzoic Acid (IBX) in a Water/CH2Cl2 Mixture in the Presence of Phase‐Transfer Catalyst

Abstract: A mild oxidation of alcohols to the respective carbonyl compounds with o-iodoxybenzoic acid (IBX) catalyzed by n-Bu 4 NBr in a water/dichloromethane (1:1) mixture is described. The method offers the advantage of a simple, inexpensive catalyst and the diminution of organic solvent employed in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The synthetic usefulness of IBX in general is significantly restricted by its low solubility in most organic solvents, with the exception of DMSO. However, in several recent reports it has been shown that IBX can be used as an effective oxidant in other than DMSO solvents. More and Finney have found that primary and secondary alcohols can be oxidized into the corresponding aldehydes or ketones in excellent yields (90−100%) by heating a mixture of the alcohol and IBX in common organic solvents . All reaction byproducts can be completely removed by filtration.…”
Section: Iodine(v) Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthetic usefulness of IBX in general is significantly restricted by its low solubility in most organic solvents, with the exception of DMSO. However, in several recent reports it has been shown that IBX can be used as an effective oxidant in other than DMSO solvents. More and Finney have found that primary and secondary alcohols can be oxidized into the corresponding aldehydes or ketones in excellent yields (90−100%) by heating a mixture of the alcohol and IBX in common organic solvents . All reaction byproducts can be completely removed by filtration.…”
Section: Iodine(v) Compoundsmentioning
confidence: 99%
“…Kuhakarn and co-workers have recently found that IBX can be used for the oxidation of alcohols in a 1:1 water/dichloromethane mixture in the presence of tetrabutylammonium bromide …”
Section: Iodine(v) Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…in 2006 reported the mild oxidation of alcohols with IBX in a water/CH 2 Cl 2 mixture in the presence of phase transfer catalyst (PTC), tetrabutylammonium bromide (TBAB) in good yields (Scheme 97). [124] …”
Section: Oxidation Reactionsmentioning
confidence: 99%